La oratoria como estrategia didáctica de enseñanza para mejorar la expresión oral de los estudiantes de la Unidad Educativa Leonardo Da Vinci - Dávila Salgado, Mayerlli Sarahí (2025)
The present research aims to analyze public speaking as a didactic strategy to improve the students' oral expression of the "Leonardo Da Vinci" Educational Unit. The justification of this study focuses on the importance of strengthening students' oral communicative skills and promoting active and participatory methodologies that favor their verbal expression in a clear, coherent, and effective manner. The study adopts a mixed approach, using an experimental methodology with a pretest-posttest design to evaluate the impact of the implementation of oratory on students' oral performance, in addition to the application of a questionnaire that allowed obtaining data on the perception of the implementation of oratorical activities in the classroom. The results showed that didactic strategies focused on public speaking significantly improved students' oral expression. In conclusion, it is recommended that educational institutions include public speaking as a fundamental strategy in the teaching process, offering continuous training to teachers to implement effective methodologies that favor students' oral expression